Resposta de células trofoblásticas bovinas à infecção por Brucella abortus: uma abordagem proteômica - Juliana Pinto da Silva Mol (2012)
Brucella abortus is considered the main etiological agent of bovine brucellosis, a zoonotic disease that causes great economic losses worldwide. The aim of this study was to determine the differential profile of proteins expression of bovine trophoblast cells in the early stages ofinfection by B. abortus. Was used the explants model prepared from chorio-alantóidea of fetuses in the last trimester of pregnancy infected by suspending the B. abortus 2308 containing 1.0 x 108 bacteria (MOI 1:1000). In the study of the kinetics of infection was evaluated the timesof 0.5, 2, 4 and 8 h post infection with B. abortus. Was obtained high reproducibility between triplicate of gels compared (Match> 84%; CI > 0.77) and the proteins expression profile was similar among the times evaluated (Match > 75%). Times of 0.5 and 4 h post infection showedthe highest qualitative differences between the gels and were used for the differential in gel electrophoresis (DIGE). In this analysis have not been identified spots with significant quantitative differences between the compared gels. Moreover, 103 spots are present only in an experimental group were selected for identification by mass spectrometry. The proteins BLVRA, LGALS7, RPLP1, SCAMP2, TOLLIP, GALM, AHCY, PSAPL1/PSAP, OAT, C1QBP, NDUFS8, PRCII, RAB11A, CALM1, MDH1, PRDX3, ABHD14B, KRT14, KRT7, HMGB1, HEXB, AKR1B1, PDIA3 and TPM4 were identified only in protein extracts of trophoblastic cells infected by B. abortus. The proteins identified in this study will serve as targets for further research related to host-pathogen interaction in infection by B. abortus.